Lyapunov exponents for higher dimensional random maps. (1997) - Góra, P.; Boyarsky, A.; Lou, Y. S.
Abstract : A random map is a discrete time dynamical system in which one of a number of transformations is selected randomly and implemented. Random maps have been used recently to model interference effects in quantum physics. The main results of this paper deal with the Lyapunov exponents for higher dimensional random maps, where the individual maps are Jabloński maps on the n -dimensional cube.